Reliability and Accuracy of Ultrasonographic Muscle Thickness Measurements: Evaluating Key Postural Stabilisers in Rehabilitation - Arkadiusz Żurawski; Natalia Barańska; Aleksandra Tomala; Edyta Majorczyk; Joanna Macierzyńska (Rehabilitacja Medyczna)
Introduction: Ultrasonography (USG) is a widely recognised, non-invasive imaging technique extensively applied in musculoskeletal diagnostics. Its capacity to provide real-time visualisation of muscle structure and function underpins its utility in clinical practice and scientific research. Nevertheless, the reliability and accuracy of USG measurements remain pivotal concerns influencing its efficacy in muscle assessment.Objective: The aim of this study is to evaluate the reliability and accuracy of USG-based muscle thickness measurements for four critical postural stabilisers: longus colli, serratus anterior, transversus abdominis and multifidus. These muscles play essential roles in postural stability due to their tonic characteristics, making them central to rehabilitation interventions.Methods: Twenty healthy participants were recruited for this investigation. Muscle thickness of the four target muscles was assessed in a resting state using standardised USG protocols. Both intra- and inter-rater reliability were analysed using Intraclass Correlation Coefficients (ICC). Measurement precision was quantified through Standard Error of Measurement (SEM) and Minimal Detectable Change (MDC), ensuring a robust evaluation of reliability metrics.Results: The analysis revealed excellent intra-rater reliability for all muscles, with ICC values ranging from 0.97 to 0.99. Inter-rater reliability was highest for the serratus anterior (ICC = 0.89-0.95) and transversus abdominis (ICC = 0.79-0.85), while moderate agreement was observed for the longus colli (ICC = 0.52-0.89). The transversus abdominis demonstrated the highest measurement precision, with the lowest Standard Error of Measurement (SEM = 0.79-1.05 mm) and Minimal Detectable Change (MDC = 2.19-2.91 mm). In contrast, the multifidus exhibited greater variability (SEM > 2.1 mm; MDC > 6.0 mm), reflecting the inherent challenges in ultrasonographic assessment of deep spinal musculature. Despite these differences, all assessed muscles achieved acceptable reliability levels, supporting the clinical utility of ultrasonography in rehabilitation monitoring.Conclusion: Ultrasonography proves to be a reliable and precise modality for assessing muscle thickness in a resting state, particularly for the transversus abdominis and serratus anterior. These findings substantiate the utility of USG in evaluating key postural stabilisers within rehabilitation settings. Standardising measurement protocols and enhancing operator training are recommended to further optimise their application and ensure consistent results.